Enrolamento das folhas da cana de açúcar - Drummond, O A (Revista Ceres, 1939)
The author describes by the first time the fungus Myriogenospora paspali Atk. attacking sugar cane in Minas Gerais. State. This species has been found on leaves of Paspalum conjugatum Aergius and Imperata Brasiliensis Trin. in the same State. This disease of sugar cane has little economic importance.